2014
DOI: 10.1088/1748-0221/9/06/p06013
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-shape discrimination and energy resolution of a liquid-argon scintillator with xenon doping

Abstract: Liquid-argon scintillation detectors are used in fundamental physics experiments and are being considered for security applications. Previous studies have suggested that the addition of small amounts of xenon dopant improves performance in light or signal yield, energy resolution, and particle discrimination. In this study, we investigate the detector response for xenon dopant concentrations from 9 ± 5 ppm to 1100 ± 500 ppm xenon (by weight) in 6 steps. The 3.14-liter detector uses tetraphenyl butadiene (TPB) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 30 publications
13
58
1
Order By: Relevance
“…This improves position reconstruction since the re-emission occurs in the point of interaction.It was shown that gaseous xenon doped in LAr works as a volume-distributed WLS shifting the wave length from 128 nm to around 175 nm [14][15][16]. Currently several groups are studying its wavelength shifting parameters and the properties of the LAr+Xe mixture [17][18][19][20]. As shown previously [21], Xe doped in small concentrations (up to 260 ppm by mass) re-emits only the slow component of LAr scintillation.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…This improves position reconstruction since the re-emission occurs in the point of interaction.It was shown that gaseous xenon doped in LAr works as a volume-distributed WLS shifting the wave length from 128 nm to around 175 nm [14][15][16]. Currently several groups are studying its wavelength shifting parameters and the properties of the LAr+Xe mixture [17][18][19][20]. As shown previously [21], Xe doped in small concentrations (up to 260 ppm by mass) re-emits only the slow component of LAr scintillation.…”
mentioning
confidence: 86%
“…As shown previously [21], Xe doped in small concentrations (up to 260 ppm by mass) re-emits only the slow component of LAr scintillation. Thus, at small concentrations it is impossible to use Xe as a single stage WLS and to keep PSD capability of the LAr+Xe mixture at the same time.In previous studies with a broad concentration range (up to 1000 ppm by mass) [19,20], it was shown that Xe-doping slightly improves the light yield and the energy resolution. Also they demonstrated that the PSD capability degrades with decreasing of Xe concentration in LAr.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The amount of energy required to form these molecules decreases for increasing Z, and the wavelength of pure helium and neon scintillation is much deeper in the UV than xenon light [13]. Data from mixtures with ∼10 ppm xenon in liquid argon show that excitations can be efficiently transferred from argon to xenon, with the resulting light emission emitted at xenon wavelengths [14]; energy transfers from excitations of the heavy noble elements to lighter ones do not take place because they are not energetically favorable. Therefore, the wavelength of S1/S2 light in a doped LXe-TPC will be unchanged.…”
Section: Pos(ichep2016)285mentioning
confidence: 99%